1998
DOI: 10.1038/bjc.1998.756
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibitors and their future role in post-menopausal women with early breast cancer

Abstract: Summary Anastrozole is the first aromatase inhibitor to show a significant survival advantage over megestrol acetate in post-menopausal women with advanced breast cancer. The rationale for extending the use of aromatase inhibitors to the treatment of early breast cancer is based on the efficacy observed in the advanced setting, combined with good tolerability and a convenient dosing regimen. Furthermore, oestrogen deprivation by ovarian ablation (similar to oestrogen antagonism with tamoxifen) is already estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Two main categories of drugs target the dependence of malignant breast epithelial cells upon oestrogens. Aromatase inhibitors inhibit cytochrome P450 CYP-19, the enzyme that converts androgens to oestrogens, and thereby reduce circulating concentrations of tumour-promoting oestrogens ( Lonning 1998 , Santen et al . 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two main categories of drugs target the dependence of malignant breast epithelial cells upon oestrogens. Aromatase inhibitors inhibit cytochrome P450 CYP-19, the enzyme that converts androgens to oestrogens, and thereby reduce circulating concentrations of tumour-promoting oestrogens ( Lonning 1998 , Santen et al . 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Letrozole, as well as anastrozole, are competitive aromatase inhibitors with high potency and rapidly reversible action (20,21). Letrozole is readily absorbed after oral administration and it is mainly cleared by the liver with a mean half-life of approximately 45 hours.…”
mentioning
confidence: 99%
“…Anastrozole, a selective AI, is one of the most used endocrine therapies for postmenopausal FBC [58][59][60][61]. Giordano et al reported that among five ER-positive MaBC who were treated with anastrozole, three patients showed disease stabilization and two showed marked improvement; however, none of the patients achieved complete response [62].…”
Section: Sabih Et Almentioning
confidence: 99%